The role of the scout organization in reducing academic stress among university students - Nasution, Kartina Aggraini; Susanti, Eka; Tamalia, Ghita (Program Pascasarjana Universitas Negeri Yogyakarta, 2024)
This study delves into the pivotal role of the Scout organization in alleviating academic stress among students at the State Islamic University of North Sumatra, Medan. Academic stress, a physiological and emotional response to academic demands, is often characterized by anxiety, worry, avoidance behaviour, and emotional instability. This research, employing a qualitative descriptive approach, investigates how the Scout organization aids students in overcoming academic stress. The findings underscore the significant role of the Scout organization in developing not just managerial skills but also leadership skills. It provides social support, encourages physical activity and relaxation, enhances mental resilience, and fosters positive character traits. The integration of these aspects creates a supportive environment that not only alleviates stress but also enriches students' personal development. This study underscores the transformative potential of non-formal educational organizations like Scouts in building adaptive skills and resilience among students, thereby enhancing student well-being and academic success.